Implementasi Kebijakan Peraturan Walikota Dalam Memaksimalkan Tugas UPTD Pengelolaan Sampah di Kota Binjai - Prayuda, Dhimas (Universitas Muhammadiyah Sumatera Utara, 2025)
Binjai City is an area located in North Sumatra Province, but it is not free from rubbish. Waste is one of the main problems that arises as a result of human activities. The increasing human population causes an increase in human activity which also increases the remaining results of human activity itself, as well as sources of the results of human activity and natural processes which are considered to have no economic value, and can even have negative economic value because they require quite large management costs. . In order to realize good waste management, this is the aim of implementing Law Number 18 of 2008 concerning Waste Management in the City of Binjai. To find out the obstacles faced by the City Government, especially the Binjai City Environmental Service, in carrying out its authority and the regulations implemented. Method The research that will be used in this thesis is a descriptive method with qualitative analysis. Data analysis is used by reviewing the results of interviews which include strategic aspects in the system or process of implementing policies, goals and objectives to be achieved in implementing policies, the process of implementing and maximizing functional and main tasks. The theory that I use is Tachjan, which in terms of the level of success of an implementation is the implementation element, the program being implemented, the target group and the presence of environmental, social, cultural and political factors. From the results of the study or analysis of data from interviews regarding these aspects, it was concluded that the implementation of Binjai Mayor Regulation No. 18 of 2008 concerning Waste Management in Binjai City carried out by the Binjai City Environmental Service has generally gone well, but there are still shortcomings and Obstacles in its implementation are caused by several factors such as deficiencies in facilities that hinder effectiveness in controlling, lack of employee performance, unclear financial funds, less effective communication and information towards the community, and policies that have never been updated.